Maybe one day - Bybee, Catherine (Bybee, Catherine. D'Angelos series., 2025)
"Mari D'Angelo's life is complete. Her children are all married. Two grandbabies fill her days, with two more on the way, and her thriving family restaurant is running on autopilot. Not once in the ten years since she's become a widow has Mari considered another love of her own. Until she sets sail on a singles cruise to placate her recently divorced best friend. Then James comes crashing into Mari's world. Charming, witty, and with two daughters of his own, James isn't looking for love either. But Mari is as irresistible as she is beautiful. As their simmering attraction grows, Mari's resolve to ignore the spark James has ignited slowly breaks away. She promised her beloved late husband she'd find someone new. Maybe that impossible day has come. Knowing her protective sons would not approve, Mari chooses to keep the romance a secret. After all, there is no reason for her family to know about James if their relationship doesn't work out. It's up to James to prove he can be trusted with the heart of a woman he's come to cherish. But without her family's approval, their love doesn't stand a chance." --